Evaluation of the impact of immediate versus WHO recommendations-guided antiretroviral therapy initiation on HIV incidence: the ANRS 12249 TasP (Treatment as Prevention) trial in Hlabisa sub-district, KwaZulu-Natal, South Africa: study protocol for a cluster randomised controlled trial. - (:unkn) unknown (My University, 2013)
BACKGROUND: Antiretroviral therapy (ART) suppresses HIV viral load in all body compartments and so limits the risk of HIV transmission. It has been suggested that ART not only contributes to preventing transmission at individual but potentially also at population level. This trial aims to evaluate the effect of ART initiated immediately after identification/diagnosis of HIV-infected individuals, regardless of CD4 count, on HIV incidence in the surrounding population. The primary outcome of the overall trial will be HIV incidence over two years. Secondary outcomes will include i) socio-behavioural outcomes (acceptability of repeat HIV counselling and testing, treatment acceptance and linkage to care, sexual partnerships and quality of life); ii) clinical outcomes (mortality and morbidity, retention into care, adherence to ART, virologic failure and acquired HIV drug resistance), iii) cost-effectiveness of the intervention. The first phase will specifically focus on the trial's secondary outcomes. METHODS/DESIGN: A cluster-randomised trial in 34 (2 × 17) clusters within a rural area of northern KwaZulu-Natal (South Africa), covering a total population of 34,000 inhabitants aged 16 years and above, of whom an estimated 27,200 would be HIV-uninfected at start of the trial. The first phase of the trial will include ten (2 × 5) clusters. Consecutive rounds of home-based HIV testing will be carried out. HIV-infected participants will be followed in dedicated trial clinics: in intervention clusters, they will be offered immediate ART initiation regardless of CD4 count and clinical stage; in control clusters they will be offered ART according to national treatment eligibility guidelines (CD4 <350 cells/μL, World Health Organisation stage 3 or 4 disease or multidrug-resistant/extensively drug-resistant tuberculosis). Following proof of acceptability and feasibility from the first phase, the trial will be rolled out to further clusters. DISCUSSION: We a
Keywords: African Research